Essays on land-use change and greenhouse gas emissions in Brazil - Silva, Jonathan Gonçalves da (2015)
This study evaluates the land use changes and forests in Brazil, focusing on deforestation and its greenhouse gas emissions (GHG). More specifically, it analyses: (i) how the specialized literature integrates land-use changes to GHG emissions into a computable general equilibrium (CGE) framework; and (ii) the economic impacts of halting the deforestation. For this purpose, this study was divided into three independent essays. The first essay is theoretical, and evaluates the state of the art of the integration between land-use change and GHG emissions into CGE models. The second essay, is an empirical study about the economic impacts of zero deforestation in the Amazon Biome. The third essay, evaluates the implication of productivity gains in agriculture on land allocation, GHG emissions and the Brazilian economy. The results highlight the difficulties to integrate land use to its GHG emissions, as well as the effectiveness of the deforestation control in the Amazon to reduce national emissions, although it imposes losses to the economy and boosts regional inequalities. Finally, productivity gains in agriculture in turn, also may reduce the domestic emissions, but with no adverse impacts on the economy. However, such effects are limited, as they expire with the productivity gains.